Atypical leukaemia of long duration with monoclonal hypergammaglobulinaemia - Constantoulakis, M. (1970)
A patient with atypical acute leukaemia is described. This patient has, in addition, monoclonal IgG hyperglobulinaemia without myelomatous lesions and is living and well three years after diagnosis. The cell types found in the blood and in the bone marrow are atypical, and the histochemical findings are discussed. The relationship between monoclonal hypergammaglobulinaemia and malignant blood diseases is also discussed, and the literature on the subject reviewed.